2023
DOI: 10.14336/ad.2023.0106
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation Mechanism of Microglial Autophagy in the Pathology of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the progressive accumulation of abnormal protein aggregates, neuronal loss, synaptic dysfunction, and neuroinflammation. Microglia are resident macrophages of the central nervous system (CNS). Evidence has shown that impaired microglial autophagy exerts considerable detrimental impact on the CNS, thus contributing to AD pathogenesis. This review highlights the association between microglial autophagy and AD pathology, with a focus on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 114 publications
1
3
0
Order By: Relevance
“…Induces autophagy is accompanied by increased protein expressions of autophagic protein markers, including Beclin1, ATG7, ATG5, or ATG12 [46]. In the present study, the early phase of autophagosome formation is observed in microglia-specific ATG7 knockout mice and si-ATG7-transfected microglia cells [21,47].…”
Section: Discussionsupporting
confidence: 56%
“…Induces autophagy is accompanied by increased protein expressions of autophagic protein markers, including Beclin1, ATG7, ATG5, or ATG12 [46]. In the present study, the early phase of autophagosome formation is observed in microglia-specific ATG7 knockout mice and si-ATG7-transfected microglia cells [21,47].…”
Section: Discussionsupporting
confidence: 56%
“…Autophagy is a protective mechanism in the body that removes damaged organelles and abnormal proteins. Studies have shown the presence of autophagy abnormalities in AD, accompanied by neuroinflammation, clearance defects, Aβ and Tau deposition, and synaptic dysfunction ( Ou-Yang et al, 2023 ). The study has found that mitochondrial autophagy is reduced by 60% in the hippocampus of AD model mice ( Fang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…When considering microglial involvement in Tau pathology, to our knowledge there has been no specific link between microglial uptake and propagation of Tau via CME mechanisms. How microglia contribute to Tau pathology is reviewed in depth elsewhere ( Das et al, 2020 ; Ayyubova, 2023 ; Chen and Yu, 2023 ; Ou-Yang et al, 2023 ). CME in microglia needs to be further investigated to clarify what degree it and other endocytic mechanisms are disrupted in AD in relation to both Aβ and Tau pathology.…”
Section: Cme Dysfunction and Ad Cellular Disruptions Across Multiple ...mentioning
confidence: 99%